Why China Bid The Olympic Games ? - R. Syaifullah Sihombing (MultiTech Publisher, 2023)
As a develop country China hopes that by staging the 2008 Olympic Games will lead huge benefits to develop its economics’ level. Due to some different finding whether positive or negative economic impacts in hosting Olympic Games. By using article reviews this research is trying to find out about the impact of hosting Olympic Games in China it is found that the Direct benefits include the impact of the Olympics on exports, investment, employment and indirect benefits including the host city to be businesses destination, transfer technology and knowledge and tourism. On the other hand, in terms of sport reformation, it is clearly revealed that China has long been reformed its sport management since ‘Olympic movement’ was introduced.